Michaël Girardin, L’offrande et le tribut. Histoire politique de la fiscalité en Judée hellénistique et romaine (200 a.C. - 135 p.C.) - Koszałka, Łukasz (Studia Gdańskie, 2023)
Michaël Girardin, L’offrande et le tribut. Histoire politique de la fiscalité en Judée hellénistique et romaine (200 a.C. - 135 p.C.)